Conflict and Political Discourse in Kurdish Novels as an example of the novels (Ashty Kurdistan- Sagur - Kurdare) - Goran Abdullah Ahmed; Hemdad Hussen Bakir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The title of this research is "conflict and political discourse in Kurdish novels as an example of the novels (ashty Kurdistan- Sagur - Kurdare)", the purpose of this study is to analyze and analyze the most important conflicts and political discourses in the novel ( ashty Kurdistan - Sagur- kurdare) On the other hand, trying to distinguish between the political conflicts facing the writer on the one hand and the reader on the other, the main task of this research is to distinguish between the type of conflicts and the type of discourses, the content of the research. It consists of the lead and the two main sections, and the most important results will eventually be presented, with the selection of references to this research.